Affective Dilemmas: The Impact of Trait Affect and State Emotion on Sustainable Consumption Decisions in a Social Dilemma Task. Issue 1 (January 2020) - Tarditi, Céline; Hahnel, Ulf J. J.; Jeanmonod, Noémie; Sander, David; Brosch, Tobias
Developing a more sustainable lifestyle is becoming an important challenge of our times; it is thus crucial to understand the factors that drive resource consumption decisions. We investigated the impact of trait affect and state emotion on individual consumption decisions in social dilemma tasks. Affective factors interacted strongly with the specific structural features of the choice situation. In Experiment 1, participants with high trait affect were especially likely to reduce their consumption when resource scarcity increased, but only when the choice was presented in a gain frame. In Experiment 2, induced guilt led to reduced consumption in the gain frame in participants with high trait affect, whereas induced pride led to increased investments in the loss frame in these participants. Our research highlights the adaptive function of affective factors in decision making in social dilemma tasks and illustrates how emotions may be leveraged to promote more sustainable resource consumption.